2007
DOI: 10.1016/j.jmaa.2006.09.043
|View full text |Cite
|
Sign up to set email alerts
|

Existence of solutions for impulsive partial neutral functional differential equations

Abstract: This paper is concerned with partial neutral functional differential equations of first and second order with impulses. We establish some results of existence of mild solutions for these classes of equations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
71
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(85 citation statements)
references
References 33 publications
3
71
0
6
Order By: Relevance
“…In this section we discuss a partial differential equation applying the abstract results of this paper. In this application, B is the phase space 0 × 2 (ℎ, ) (see [10]). …”
Section: Examplesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section we discuss a partial differential equation applying the abstract results of this paper. In this application, B is the phase space 0 × 2 (ℎ, ) (see [10]). …”
Section: Examplesmentioning
confidence: 99%
“…For details see [7][8][9][10][11][12]. As a matter of fact, in these papers their authors assume severe conditions on the operator family generated by , which imply that the underlying space has finite dimension.…”
Section: Introductionmentioning
confidence: 99%
“…The existence of almost periodic solutions for abstract impulsive dynamic equations was considered by many authors; see [10,16,24,25]. To the best of our knowledge, weighted piecewise pseudo double-almost periodic solutions for impulsive dynamic equations on ACCTS have never been considered in any literature.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable work in the field of fixed impulsive type equations may be found in [9,16] and the references therein. The study of impulsive stochastic differential equations (ISDEs) is a new area of research and few publications on that subject can be found in the literature.…”
Section: Introductionmentioning
confidence: 99%